Link between perceived oral and general health status among Yemeni adult dental patients - Mohammed Nasser Alhajj; Esam Halboub; Abdullah G. Amran; Abdulaziz A. Alkheraif; Fuad A. Al-Sanabani; Bandar M. Al-Makramani; Abdulghani A. Al-Basmi; Fawaz A. Al-Ghabri (BMC, 2019)
Abstract Background Self-perceived health is an essential measure of health status and even a paramount predictor of mortality. So long as it is said that oral health (OH) and general health (GH) are mirrors to each other. This study sought to determine how Yemeni adults rate their OH and GH, whether such a self-rating influenced by some potential risk factors, and whether both ratings (OH and GH) are correlated. Methods A sample of 587 Yemeni dental patients aged 20 years and over were consecutively recruited. A structured interview form was used covering the following variables: age, gender, marital status, educational level, presence of dental prosthesis (DP), smoking and Qat chewing habits as independent variables, along with questions on "perceived oral health (POH)" and "perceived general health (PGH)" as dependent variables. The bivariate and multiple ordinal regression analyses were applied at P-value < 0.05. Results Most of participants were women (73.6%), and married (71.4%), and more than half of them were young adults (58.2%), with high educational levels (53.3%), and not having DP. Only 310 participants responded to the questions on smoking and Qat chewing habits. Of these, 88.5% were non-smokers and 62.1% were Qat non-chewers. Up to 50% of the participants reported their POH as poor or fair, while lower proportions of participants (17%) reported their PGH as such. Younger age (compared to elders), high education levels (compared to primary education) and being single (compared to married) significantly revealed better levels of POH, while high education levels and being females significantly revealed better levels of PGH. Smoking and Qat chewing habits were found to have no effect on the perception of POH or PGH. POH and PGH were found to be significantly correlated (r = 0.486; P < 0.001). Conclusion Higher levels of oral health problems can be anticipated among patients who perceive poor general health, and vice versa. The age, marital status and education were independent determinants of POH, while the gender and education were independent determinants of PGH.